Transiting exoplanets from the CoRoT space mission XIV. CoRoT-11b: a transiting massive "hot-Jupiter" in a prograde orbit around a rapidly rotating F-type star - Gandolfi, D; Hébrard, G; Alonso, R; Deleuil, M; Guenther, E; Fridlund, M; Endl, M; Eigmüller, P; Csizmadia, S; Havel, M; Aigrain, S; Auvergne, M; et al. (2010)
The CoRoT exoplanet science team announces the discovery of CoRoT-11b, a fairly massive hot-Jupiter transiting a V=12.9 mag F6 dwarf star (M*=1.27 +/- 0.05 Msun, R*=1.37 +/- 0.03 Rsun, Teff=6440 +/- 120 K), with an orbital period of P=2.994329 +/- 0.000011 days and semi-major axis a=0.0436 +/- 0.005 AU. The detection of part of the radial velocity anomaly caused by the Rossiter-McLaughlin effect shows that the transit-like events detected by CoRoT are caused by a planet-sized transiting object in a prograde orbit. The relatively high projected rotational velocity of the star (vsini=40+/-5 km/s) places CoRoT-11 among the most rapidly rotating planet host stars discovered so far. With a planetary mass of mp=2.33+/-0.34 Mjup and radius rp=1.43+/-0.03 Rjup, the resulting mean density of CoRoT-11b (rho=0.99+/-0.15 g/cm^3) can be explained with a model for an inflated hydrogen-planet with a solar composition and a high level of energy dissipation in its interior.